3D-CuZnAlMg catalyst and preparation method and application thereof

The 3D-CuZnAlMg catalyst prepared by 3D printing technology solves the problem of the reduction of selectivity of existing catalysts under high temperature conditions, and achieves efficient CO2 hydrogenation to methanol reaction, which improves the activity and stability of the catalyst.

CN119386877APending Publication Date: 2025-02-07HUANENG CLEAN ENERGY RES INST +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523131.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing catalysts increase CO selectivity under high temperature conditions, resulting in a decrease in methanol selectivity, and copper-based catalysts form water at active sites resulting in inactivation.

Method used

The catalyst particles are prepared by 3D printing technology by using 3D-CuZnAlMg catalyst, which changes the mass transfer method of the catalyst, improves the catalytic efficiency, and improves the activity and stability of the catalyst through the combination of CuO, ZnO, Al2O3 and MgO.

Benefits of technology

The selectivity of methanol and CO2 conversion rate are significantly improved, the selectivity of by-product CO is reduced, and the catalyst has higher activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386877A_ABST
    Figure CN119386877A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of methanol preparation through CO2 hydrogenation, and particularly relates to a 3D-CuZnAlMg catalyst as well as a preparation method and application thereof. The preparation method of the 3D-CuZnAlMg catalyst, provided by the invention, comprises the following steps: (1) dissolving Cu (NO3) 2, Zn (NO3) 2, Al (NO3) 3 and Mg (NO3) 2 into deionized water according to a ratio, and carrying out ultrasonic water bath treatment to obtain molten metal; (2) adding a precipitant into the molten metal for precipitation reaction, and then performing aging treatment and filtering to obtain a solid material; (3) carrying out washing treatment and first drying treatment on the solid material to obtain a catalyst precursor, and carrying out first calcining treatment on the catalyst precursor to obtain a CuZnAlMg catalyst; and (4) mixing the CuZnAlMg catalyst and polyvinyl alcohol, then carrying out 3D printing, and carrying out secondary drying treatment and secondary calcining treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing methanol by hydrogenating CO2, and specifically relates to a 3D-CuZnAlMg catalyst and a preparation method and application thereof. Background Art

[0002] The capture and collection of CO2 is a potential solution to address global climate change and reduce greenhouse gas emissions. Directly converting green hydrogen produced by renewable energy into high-value-added chemicals by coupling CO2 is of great significance for achieving the country's "dual carbon" goals, reducing CO2 emissions, establishing a sustainable carbon cycle, solving environmental problems, and producing high-value-added chemicals.

[0003] Among them, CO2 hydrogenation to methanol is one of the effective ways to utilize CO2 resources. Methanol is one of the most important bulk chemicals in the chemical industry and an important clean chemical raw material for the manufacture of other chemicals. CO2 hydrogenation to methanol has attracted increasing interest in the past two decades. It is worth mentioning that many research works are devoted to exploring high-activity catalysts for CO2 hydrogenation to methanol in order to improve the conversion rate of CO2 and methanol selectivity.

[0004] At lower temperatures (below 250°C) and higher pressures, the use of copper-based catalysts is beneficial for hydrogenating carbon dioxide to produce methanol. However, at higher temperatures, byproducts other than methanol are formed, thereby reducing the amount of methanol formed. In addition, deactivation of the copper-based catalyst may occur due to the formation of water on the active copper sites.

[0005] Therefore, more and more technicians are committed to studying new catalysts for the hydrogenation of carbon dioxide to methanol. Summary of the invention

[0006] The present invention is based on the inventor's discovery and understanding of the following facts and problems:

[0007] CO2 is a typical linear symmetrical molecule. The chemical inertness of CO2 molecules leads to low CO2 hydrogenation reaction conversion rate and low methanol selectivity. Although the existing catalysts are conducive to the synthesis of methanol at lower reaction temperatures and higher reaction pressures, they are limited by the reaction kinetics under such conditions. Although the CO2 conversion rate will be improved under high temperature conditions, the reverse water gas shift reaction will increase CO selectivity under high temperature conditions, and the selectivity of the target product methanol will be reduced.

[0008] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the embodiments of the present invention provide a 3D-CuZnAlMg catalyst, which has higher catalytic activity and stability and improves the selectivity of the current product methanol.

[0009] The embodiment of the present invention also provides a method for preparing a 3D-CuZnAlMg catalyst, comprising the following steps:

[0010] (1) dissolving Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Mg(NO3)2 in deionized water according to a ratio and subjecting the mixture to ultrasonic water bath treatment to obtain a molten metal;

[0011] (2) adding a precipitant to the molten metal obtained in step (1) to carry out a precipitation reaction, and then performing an aging treatment and filtering to obtain a solid material;

[0012] (3) washing the solid material obtained in step (2) and performing a first drying treatment to obtain a catalyst precursor, and performing a first calcination treatment on the catalyst precursor to obtain a CuZnAlMg catalyst;

[0013] (4) The CuZnAlMg catalyst prepared in step (3) is mixed with polyvinyl alcohol and then 3D printed, and a second drying treatment and a second calcination treatment are performed to obtain a 3D-CuZnAlMg catalyst.

[0014] The advantages and technical effects brought by the preparation method of the 3D-CuZnAlMg catalyst of the embodiment of the present invention are as follows: 1. The method of the embodiment of the present invention further adopts a 3D printing method to prepare catalyst particles, changes the mass transfer of the catalyst during the reaction, and significantly improves the catalytic efficiency; 2. The method of the embodiment of the present invention is based on 3D printing catalyst preparation technology controlled by a computer program, and has the advantages of high production efficiency, low manufacturing cost, and flexible construction of a designable three-dimensional structure. The prepared catalyst has better catalytic activity and stability.

[0015] In some embodiments, in step (1), the mass ratio of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Mg(NO3)2 is 7-12:3-6:1-4:0.5-4;

[0016] And / or, in step (1), the solid-to-liquid ratio of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Mg(NO3)2 and deionized water is 1g: (10-30)mL;

[0017] And / or, in the step (1), the temperature of the ultrasonic water bath treatment is 60-70° C., the ultrasonic power is 180-240 W, and the time of the ultrasonic water bath treatment is 0.5-3 h.

[0018] In some embodiments, in step (2), the precipitant is a 0.5-3 mol / L Na2CO3 solution, and the volume ratio of the molten metal to the precipitant is 1:(1.5-2);

[0019] And / or, the pH of the precipitation reaction is 8 to 10, the temperature of the precipitation reaction is 60 to 80° C., and the time of the precipitation reaction is 2 to 4 hours;

[0020] And / or, the aging treatment is carried out in a water bath at 60-70° C. for 10-14 hours.

[0021] In some embodiments, in step (3), the temperature of the first drying treatment is 80 to 100° C., and the time of the first drying treatment is 10 to 16 hours;

[0022] And / or, the temperature of the first calcination treatment is 400-500° C., and the time of the first calcination treatment is 6-10 hours.

[0023] In some embodiments, in step (4), the mass ratio of the CuZnAlMg catalyst to polyvinyl alcohol is (40-50): (4-6);

[0024] And / or, the temperature of the second drying treatment is 40-60° C., and the time of the second drying treatment is 8-14 hours;

[0025] And / or, the temperature of the second calcination treatment is 750-900° C., and the time of the second calcination treatment is 1-4 hours.

[0026] In some embodiments, in step (4), the 3D printing further comprises: first 3D printing the mixture of CuZnAlMg catalyst and polyvinyl alcohol into a column, and cutting the column into particles; the column has a diameter of 0.5 to 2 mm and a length of 8 to 12 cm, and the particles have a diameter of 0.5 to 2 mm and a length of 0.5 to 2 mm;

[0027] And / or, the 3D printing speed is 15-25 mm / s.

[0028] The embodiment of the present invention further provides a 3D-CuZnAlMg catalyst, which is prepared by the above method.

[0029] In some embodiments, the 3D-CuZnAlMg catalyst includes: CuO, ZnO, Al2O3, MgO, wherein the content of CuO is 60-75wt%, the content of ZnO is 18-28wt%, the content of Al2O3 is 5-10wt%, and the content of MgO is 1-3wt%. In the catalyst, Cu acts as an active site for H2 adsorption, while ZnO and MgO act as additives, promoting the adsorption of CO2 by the Cu active site, so that CO2 can react with H2 and eventually produce methanol. In addition, the combination of ZnO or MgO and Cu also serves as a carrier, which is beneficial to the dispersion and stabilization of the Cu active site. Al2O3, as a structural additive, can improve the dispersibility of Cu species, increase the specific surface area of ​​the catalyst, and increase the mechanical strength of the catalyst.

[0030] The embodiments of the present invention also provide the 3D-CuZnAlMg catalyst prepared by the above method or the use of the above 3D-CuZnAlMg catalyst in the production of methanol by hydrogenation of carbon dioxide.

[0031] The embodiment of the present invention further provides a NaA molecular sieve membrane reactor, comprising the 3D-CuZnAlMg catalyst prepared by the above method or a catalytic layer formed by the above 3D-CuZnAlMg catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Schematic diagram of the membrane reactor structure, wherein 1-raw gas inlet, 2-tail gas outlet, 3-purge gas inlet, 4-purge gas outlet, 5-3D-CuZnAlMg catalyst and quartz sand (● represents 3D-CuZnAlMg catalyst; ○ represents quartz sand), 6-purge gas channel; 7-porous support; 8-NaA-molecular sieve membrane, 9-cavity;

[0033] Figure 2 XRD spectra of 3D-CuZnAlMg catalyst before and after high-purity H2 reduction and reaction with feed gas;

[0034] Figure 3 This is a schematic diagram showing the effect of the 3D-CuZnAlMg catalyst prepared in Example 3 on methanol selectivity and carbon dioxide conversion rate as a function of reaction time. DETAILED DESCRIPTION

[0035] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0036] The embodiment of the present invention also provides a method for preparing a 3D-CuZnAlMg catalyst, comprising the following steps:

[0037] (1) dissolving Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Mg(NO3)2 in deionized water according to a ratio and subjecting the mixture to ultrasonic water bath treatment to obtain a molten metal;

[0038] (2) adding a precipitant to the molten metal obtained in step (1) to carry out a precipitation reaction, and then performing an aging treatment and filtering to obtain a solid material;

[0039] (3) washing the solid material obtained in step (2) and performing a first drying treatment to obtain a catalyst precursor, and performing a first calcination treatment on the catalyst precursor to obtain a CuZnAlMg catalyst;

[0040] (4) The CuZnAlMg catalyst prepared in step (3) is mixed with polyvinyl alcohol and then 3D printed, and a second drying treatment and a second calcination treatment are performed to obtain a 3D-CuZnAlMg catalyst.

[0041] The preparation method of the 3D-CuZnAlMg catalyst of the embodiment of the invention further adopts a 3D printing method to prepare catalyst particles, and changes the mass transfer of the catalyst during the reaction process, so that the catalytic efficiency is significantly improved; the method of the embodiment of the present invention is based on 3D printing catalyst preparation technology controlled by a computer program, and has the advantages of high production efficiency, low manufacturing cost and flexible construction of a designable three-dimensional structure. The prepared catalyst has better catalytic activity and stability.

[0042] In some embodiments, preferably, in the step (1), the mass ratio of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Mg(NO3)2 is 7-12:3-6:1-4:0.5-4.

[0043] In some embodiments, preferably, in the step (1), the solid-to-liquid ratio of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Mg(NO3)2 and deionized water is 1g:(10-30)mL.

[0044] In some embodiments, preferably, the temperature of the ultrasonic water bath treatment is 60-70° C., the ultrasonic power is 180-240 W, and the time of the ultrasonic water bath treatment is 0.5-3 h.

[0045] In some embodiments, preferably, in the step (2), the precipitant is a 0.5-3 mol / L Na2CO3 solution, and the volume ratio of the molten metal to the precipitant is 1:(1.5-2);

[0046] And / or, the pH of the precipitation reaction is 8 to 10, the temperature of the precipitation reaction is 60 to 80° C., and the time of the precipitation reaction is 2 to 4 hours;

[0047] And / or, the aging treatment is carried out in a water bath at 60-70° C. for 10-14 hours.

[0048] In some embodiments, preferably, in the step (2), after the precipitant is added to the molten metal, a NaOH solution is added to adjust the pH of the system to 8-10.

[0049] In some embodiments, preferably, in step (3), the temperature of the first drying treatment is 80-100° C., and the time of the first drying treatment is 10-16 hours;

[0050] And / or, the temperature of the first calcination treatment is 400-500° C., and the time of the first calcination treatment is 6-10 hours.

[0051] In some embodiments, preferably, in the step (4), the mass ratio of the CuZnAlMg catalyst to polyvinyl alcohol is (40-50): (4-6);

[0052] And / or, the temperature of the second drying treatment is 40-60° C., and the time of the second drying treatment is 8-14 hours;

[0053] And / or, the temperature of the second calcination treatment is 750-900° C., and the time of the second calcination treatment is 1-4 hours.

[0054] In some embodiments, preferably, in step (4), the 3D printing further comprises: first 3D printing the mixture of CuZnAlMg catalyst and polyvinyl alcohol into a column, and cutting the column into particles; the column has a diameter of 0.5 to 2 mm and a length of 8 to 12 cm, and the particles have a diameter of 0.5 to 2 mm and a length of 0.5 to 2 mm;

[0055] And / or, the 3D printing speed is 15-25 mm / s.

[0056] The embodiment of the present invention further provides a 3D-CuZnAlMg catalyst, which is prepared by the above method.

[0057] In some embodiments, the 3D-CuZnAlMg catalyst includes: CuO, ZnO, Al2O3, MgO, wherein the content of CuO is 60-75wt%, the content of ZnO is 18-28wt%, the content of Al2O3 is 5-10wt%, and the content of MgO is 1-3wt%. In the catalyst, Cu acts as an active site for H2 adsorption, while ZnO and MgO act as additives, promoting the adsorption of CO2 by the Cu active site, so that CO2 can react with H2 and eventually produce methanol. In addition, the combination of ZnO or MgO and Cu also serves as a carrier, which is beneficial to the dispersion and stabilization of the Cu active site. Al2O3, as a structural additive, can improve the dispersibility of Cu species, increase the specific surface area of ​​the catalyst, and increase the mechanical strength of the catalyst.

[0058] The embodiments of the present invention also provide the 3D-CuZnAlMg catalyst prepared by the above method or the use of the above 3D-CuZnAlMg catalyst in the production of methanol by hydrogenation of carbon dioxide.

[0059] A NaA molecular sieve membrane reactor comprises the 3D-CuZnAlMg catalyst prepared by the above method or a catalytic layer formed by the above 3D-CuZnAlMg catalyst.

[0060] The structural schematic diagram of the NaA molecular sieve membrane reactor is as follows Figure 1 As shown, the NaA molecular sieve membrane reactor includes a cavity 9 and a catalytic unit 5 and a membrane permeation unit located inside the cavity 9. The cavity 9 is a columnar cavity, and the membrane permeation unit runs through the length direction of the cavity 9; one end of the cavity 9 is provided with a raw gas inlet 1 for introducing CO2 and H2, and the other end is provided with a tail gas outlet 2 for discharging tail gas; a cold trap is arranged before the tail gas outlet 2, and methanol is liquefied by introducing circulating water to the outside of the cold trap, and then collected in the cold trap.

[0061] The membrane permeation unit includes a porous support 7 and a NaA molecular sieve membrane 8 loaded on the surface of the porous support 7. A purge gas channel 6 is formed inside the porous support 7. A purge gas inlet 3 is provided at one end of the porous support 7 for introducing purge gas, and a purge gas outlet 4 is provided at the other end for removing water vapor.

[0062] The catalytic unit 5 is located in the inner area of ​​the cavity 9 outside the membrane permeation unit, and the catalytic unit 5 includes the above-mentioned 3D-CuZnAlMg and quartz sand.

[0063] The NaA molecular sieve membrane 8 is a tubular NaA molecular sieve membrane with a length of 12 cm and an inner diameter of 8.5 mm.

[0064] The preparation method of the NaA molecular sieve membrane-8 comprises the following steps:

[0065] (a) mixing sodium aluminate, sodium hydroxide, silica sol and deionized water in a molar ratio of 1.2:5:60:1000 and stirring to prepare a clear sol, reacting at 90° C. for 5 hours to form a mother liquor containing seed crystals;

[0066] (b) vertically immersing an α-Al2O3 membrane tube (pore size 110 nm, provided by Nanjing Hongyi Ceramic Nanofiltration Membrane Co., Ltd.) sealed at both ends into the mother solution obtained in step (a) for 20 seconds by using a Czochralski method, and then naturally drying it at room temperature after taking it out;

[0067] (c) placing the membrane tube in the clarified sol described in step (a) again and reacting at 100° C. for 8 h to obtain a NaA molecular sieve membrane.

[0068] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0069] Example 1

[0070] (1) 10.63 g Cu(NO3)2·3H2O, 3.66 g Zn(NO3)2·6H2O, 2.94 g Al(NO3)3·9H2O and 0.64 g Mg(NO3)2·6H2O were dissolved in 200 mL of deionized water, and subjected to ultrasonic water bath treatment at 65°C for 1 h, wherein the ultrasonic frequency was 200 W, to obtain a molten metal;

[0071] (2) adding 270 mL of 2 mol / L Na2CO3 solution to the molten metal obtained in step (1), adjusting the pH of the system to 9.0 by dropwise adding 1 mol / L NaOH solution, raising the temperature to 70° C. to carry out precipitation reaction for 3 h, then aging in a 70° C. water bath for 12 h, and filtering to obtain the material;

[0072] (3) washing the material obtained in step (2) with deionized water, drying it at 90° C. for 12 h to obtain a catalyst precursor, and calcining the catalyst precursor at 500° C. for 8 h to obtain a CuZnAlMg catalyst;

[0073] (4) 50 g of the CuZnAlMg catalyst obtained in step (3) and 4 g of polyvinyl alcohol were mixed and 3D printed at a speed of 20 mm / s to form a column with a diameter of 1 mm and a length of 10 cm. The column was cut into pellets with a diameter of 1 mm and a length of 1 mm, and dried at 50°C for 10 h. The final catalyst product was obtained after calcination at 800°C for 2 h, which was recorded as 3D-CuZnAlMg catalyst.

[0074] The catalyst prepared in this embodiment includes: CuO, ZnO, Al2O3, MgO, wherein the content of CuO is 70wt%, the content of ZnO is 20wt%, the content of Al2O3 is 8wt%, the content of MgO is 2wt%, and the catalyst product is a particle with a diameter of 1mm and a length of 1mm.

[0075] Example 2

[0076] The preparation method of this embodiment is the same as that of Example 1, except that in step (1), 9.57 g Cu(NO3)2·3H2O, 4.39 g Zn(NO3)2·6H2O, 3.68 g Al(NO3)3·9H2O and 0.96 g Mg(NO3)2·6H2O.

[0077] The catalyst prepared in this embodiment includes: CuO, ZnO, Al2O3, and MgO, wherein the content of CuO is 63wt%, the content of ZnO is 24wt%, the content of Al2O3 is 10wt%, and the content of MgO is 3wt%, wherein the catalyst product is a particle with a diameter of 1mm and a length of 1mm.

[0078] Example 3

[0079] The preparation method of this embodiment is the same as that of Embodiment 1, except that in step (4), the 3D printing speed is 15 mm / s.

[0080] Example 4

[0081] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (4), the calcination temperature is 900° C. and the calcination time is 1 h.

[0082] Comparative Example 1

[0083] The preparation method of this comparative example is the same as that of Example 1, except that in step (1): 7.59g Cu(NO3)2·3H2O, 5.49g Zn(NO3)2·6H2O, 3.68g Al(NO3)3·9H2O and 3.20g Mg(NO3)2·6H2O.

[0084] The catalyst prepared in this comparative example includes: CuO, ZnO, Al2O3, and MgO, wherein the content of CuO is 50wt%, the content of ZnO is 30wt%, the content of Al2O3 is 10wt%, and the content of MgO is 10wt%, wherein the catalyst product is a particle with a diameter of 1mm and a length of 1mm.

[0085] Comparative Example 2

[0086] The preparation method of this comparative example is the same as that of Example 1, except that: in step (1), 9.11g Cu(NO3)2·3H2O, 5.49g Zn(NO3)2·6H2O, 1.84g Al(NO3)3·9H2O and 1.60g Mg(NO3)2·6H2O.

[0087] The catalyst prepared in this comparative example includes: CuO, ZnO, Al2O3, and MgO, wherein the content of CuO is 60wt%, the content of ZnO is 30wt%, the content of Al2O3 is 5wt%, and the content of MgO is 5wt%, wherein the catalyst product is a particle with a diameter of 1mm and a length of 1mm.

[0088] Comparative Example 3

[0089] The preparation method of this comparative example is the same as that of Example 1, except that step (4) is omitted, that is, after the CuZnAlMg catalyst is obtained, 3D printing is not performed.

[0090] Comparative Example 4

[0091] The preparation method of this comparative example is the same as that of Example 1, except that in step (4), a tabletting granulation method is used to prepare particles with a diameter of 1 mm and a length of 1 mm.

[0092] Application Example 1

[0093] (1) Preparation of NaA molecular sieve membrane: (a) Sodium aluminate, sodium hydroxide, silica sol and deionized water were mixed and stirred in a molar ratio of 1.2:5:60:1000 to prepare a clear sol, and reacted at 90°C for 5 hours to form a mother liquor containing seed crystals; (b) An α-Al2O3 membrane tube (pore size of 110 nm, provided by Nanjing Hongyi Ceramic Nanofiltration Membrane Co., Ltd.) sealed at both ends was vertically immersed in the mother liquor obtained in step (a) for 20 seconds by a pulling method, and then naturally dried at room temperature after being taken out; (c) The membrane tube was placed in the clear sol described in step (a) again, and reacted at 100°C for 8 hours to obtain a NaA molecular sieve membrane.

[0094] (2) 2.0 g of the 3D-CuZnAlMg catalyst prepared in Example 1 and 15.0 g of quartz sand were placed in a membrane reactor device for reduction, wherein the tube material in the membrane reactor device was the NaA molecular sieve membrane material prepared in step (1) with a carrier. High-purity H2 was introduced into the membrane reactor device (a tubular reactor with a tube length of 12 cm and an inner diameter of 8.5 mm) at a space velocity of W / F=10 h, and the reduction temperature of the membrane reactor device was controlled to be 300° C. (programmed temperature), the pressure was 0.2 MPa, and the introduction time was 6 h, so that the inner cavity and the outer cavity of the membrane reactor device maintained a reducing atmosphere.

[0095] (3) After the reduction is completed, the temperature is lowered and the reaction is switched to raw gas. The raw gas composition is CO2 / H2 / N2=24 / 72 / 4 (W / F=10h), and the purge gas is high-purity He (W / F=50h). The purpose of the purge gas is to promptly remove the H2O and methanol that penetrate from the outside of the tube. The reaction temperature is 200°C and the reaction pressure is 3MPa. The reaction results are shown in Table 1.

[0096] Application Example 2

[0097] The difference from Application Example 1 is that in the membrane reactor device of step (3), the raw gas W / F=15h. The reaction results are shown in Table 1.

[0098] Application Example 3

[0099] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction temperature is 250° C. The reaction results are shown in Table 1.

[0100] Application Example 4

[0101] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction temperature is 250°C, the raw gas W / F=15h, and the reaction pressure is 2MPa. The reaction results are shown in Table 1.

[0102] Application Example 5

[0103] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction temperature is 280° C. The reaction results are shown in Table 1.

[0104] Application Example 6

[0105] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction temperature is 280°C, and the raw gas W / F=15h. The reaction results are shown in Table 1.

[0106] Application Example 7

[0107] The difference from Application Example 1 is that in step (3) the reaction temperature in the membrane reactor device is 300° C. The reaction results are shown in Table 1.

[0108] Application Example 8

[0109] The difference from Example 1 is that in the membrane reactor device of step (3), the reaction temperature is 300°C and the raw gas W / F=15h. The reaction results are shown in Table 1.

[0110] Application Example 9

[0111] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction temperature is 180° C. The reaction results are shown in Table 1.

[0112] Application Example 10

[0113] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction pressure is 2 MPa. The reaction results are shown in Table 1.

[0114] Application Example 11

[0115] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction pressure is 4 MPa. The reaction results are shown in Table 1.

[0116] Application Example 12

[0117] The difference from Application Example 1 is that in step (3) of the membrane reactor device, the reaction pressure is 5 MPa. The reaction results are shown in Table 1.

[0118] Application Example 13

[0119] The difference from Application Example 1 is that in the membrane reactor device of step (3), the reaction pressure is 1 MPa. The reaction results are shown in Table 1.

[0120] Application Example 14

[0121] The difference from Application Example 1 is that in the membrane reactor device of step (3), the raw gas W / F=5h. The reaction results are shown in Table 1.

[0122] Application Example 15

[0123] The difference from Application Example 1 is that in the membrane reactor device of step (3), the raw gas W / F=8h. The reaction results are shown in Table 1.

[0124] Application Example 16

[0125] The difference from Application Example 1 is that in the membrane reactor device of step (3), the raw gas W / F=20h. The reaction results are shown in Table 1.

[0126] Application Example 17

[0127] The difference from Application Example 1 is that in the membrane reactor device of step (3), the raw gas W / F=2h. The reaction results are shown in Table 1.

[0128] Application Example 18

[0129] The difference from Application Example 1 is that the 3D-CuZnAlM catalyst prepared in Example 2 is used in step (2). The reaction results are shown in Table 1.

[0130] Application Example 19

[0131] The difference from Application Example 1 is that the 3D-CuZnAlMg catalyst prepared in Example 3 is used in step (2).

[0132] Application Example 20

[0133] The difference from Application Example 1 is that the 3D-CuZnAlMg catalyst prepared in Example 4 is used in step (2). The reaction results are shown in Table 1.

[0134] Application Comparative Example 1

[0135] The difference from Application Example 1 is that the 3D-CuZnAlMg catalyst prepared in Comparative Example 1 is used in step (2). The reaction results are shown in Table 1.

[0136] Application Comparative Example 2

[0137] The difference from Application Example 1 is that the 3D-CuZnAlMg catalyst prepared in Comparative Example 2 is used in step (2). The reaction results are shown in Table 1.

[0138] Application Comparative Example 3

[0139] The difference from Application Example 1 is that the CuZnAlMg catalyst prepared in Comparative Example 3 is used in step (2). The reaction results are shown in Table 1.

[0140] Application Comparative Example 4

[0141] The difference from Application Example 1 is that the CuZnAlMg catalyst prepared in Comparative Example 4 is used in step (2). The reaction results are shown in Table 1.

[0142] Application Comparative Example 5

[0143] The difference from Application Example 1 is that step (2) is a conventional fixed bed reactor, the reaction temperature in step (3) is 200° C., and the reaction results are shown in Table 1.

[0144] Application Comparative Example 6

[0145] The difference from Application Example 1 is that the CuZnAlMg catalyst prepared in Comparative Example 4 is used in step (2), step (2) is a conventional fixed bed reactor, the reaction temperature in step (3) is 200°C, and the reaction results are shown in Table 1.

[0146] Table 1

[0147]

[0148]

[0149] It can be seen from the catalyst performance evaluation results in Table 1 that the 3D-CuZnAlMg catalyst provided by the present invention promotes the reaction in the direction of methanol production by continuously removing the byproduct water in the NaA molecular sieve membrane reactor, and has excellent CO2 hydrogenation to methanol catalytic performance, CO2 conversion rate can reach 25.36%, methanol selectivity is 81.02-96.36%; while the byproduct CO selectivity is as low as 7.64-18.98%, and the maximum methanol yield reaches 23.42%. Compared with application examples 1-20, the CO2 conversion rate and methanol selectivity of comparative examples 1-2 are significantly reduced, which is mainly because the component ratio of the catalyst determines the catalytic performance of the catalyst to a large extent; while in comparative examples 3 and 4, the catalyst is not 3D printed, or only simple tableting and granulation are performed. During the reaction process, the mass transfer efficiency of the obtained catalyst is low, which significantly reduces the activity of the catalyst. In the application comparative example 5, a conventional fixed bed reactor was used, and the CO2 conversion rate was only 7.43%, the methanol selectivity was only 68.525%, and the methanol yield did not exceed 5.09%, which shows that the catalytic performance of the 3D-CuZnAlMg catalyst in the NaA molecular sieve membrane reactor is much higher than that of the conventional fixed bed reactor. From the above examples, it can be seen that the 3D-CuZnAlMg catalyst provided by the present invention is coupled with the NaA molecular sieve membrane reactor for catalyzing the CO2 to methanol reaction, and has the excellent performance of high CO2 conversion rate, high LPG selectivity and yield, and low byproduct CO selectivity.

[0150] The XRD characterization of the 3D-CuZnAlMg catalyst before and after high-purity H2 reduction and after reaction with raw gas was performed. Figure 2 As shown, from Figure 2 It can be seen that the catalyst before reduction showed weak CuO characteristic diffraction peaks at 2θ of 35.4° and 38.6°, indicating that CuO is well dispersed; after reduction with high-purity H2, the CuO diffraction peak at 2θ=38.6° of the sample was significantly reduced, and characteristic diffraction peaks of metal Cu appeared at 2θ of 43.3°, 50.4° and 73.9°; when the 3D-CuZnAlMg catalyst was evaluated for CO2 hydrogenation reaction activity, the CuO characteristic diffraction peak appeared at 2θ=38.6° again, indicating that metal Cu will be gradually oxidized during the reaction, and the characteristic diffraction peak of metal Cu at 2θ=43.3° is reduced, indicating that the reduced Cu catalyst may be further dispersed into smaller grains during the CO2 hydrogenation reaction.

[0151] The stability test of the 3D-CuZnAlMg catalyst prepared in Example 3 was carried out. The specific test method was the same as the reaction process in Application Example 1, except that in step (3), the reaction temperature was raised to 250°C, the reaction was continued for 220 hours, and data was recorded every 4 hours to calculate the methanol selectivity and carbon dioxide conversion rate and plotted. Figure 3 .from Figure 3 It can be seen that the 3D-CuZnAlMg catalyst prepared in the example of the present application has very good stability. After a reaction time of up to 220 hours, the methanol selectivity and carbon dioxide conversion rate are still stable in a relatively high range.

[0152] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0153] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a 3D-CuZnAlMg catalyst, characterized in that: The following steps are involved: (1) dissolving Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Mg(NO3)2 in deionized water according to a ratio and subjecting the mixture to ultrasonic water bath treatment to obtain a molten metal; (2) adding a precipitant to the molten metal obtained in step (1) to carry out a precipitation reaction, and then performing an aging treatment and filtering to obtain a solid material; (3) washing the solid material obtained in step (2) and performing a first drying treatment to obtain a catalyst precursor, and performing a first calcination treatment on the catalyst precursor to obtain a CuZnAlMg catalyst; (4) The CuZnAlMg catalyst prepared in step (3) is mixed with polyvinyl alcohol and then 3D printed, and a second drying treatment and a second calcination treatment are performed to obtain a 3D-CuZnAlMg catalyst.

2. The method for preparing the 3D-CuZnAlMg catalyst according to claim 1, characterized in that: In the step (1), the mass ratio of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, and Mg(NO3)2 is 7-12:3-6:1-4:0.5-4; And / or, in step (1), the solid-to-liquid ratio of Cu(NO3)2, Zn(NO3)2, Al(NO3)3, Mg(NO3)2 and deionized water is 1g: (10-30)mL; And / or, in the step (1), the temperature of the ultrasonic water bath treatment is 60-70° C., the ultrasonic power is 180-240 W, and the time of the ultrasonic water bath treatment is 0.5-3 h.

3. The method for preparing the 3D-CuZnAlMg catalyst according to claim 1, characterized in that: In the step (2), the precipitant is a 0.5-3 mol / L Na2CO3 solution, and the volume ratio of the molten metal to the precipitant is 1:(1.5-2); And / or, the pH of the precipitation reaction is 8 to 10, the temperature of the precipitation reaction is 60 to 80° C., and the time of the precipitation reaction is 2 to 4 hours; And / or, the aging treatment is carried out in a water bath at 60-70° C. for 10-14 hours.

4. The method for preparing the 3D-CuZnAlMg catalyst according to claim 1, characterized in that: In the step (3), the temperature of the first drying treatment is 80 to 100° C., and the time of the first drying treatment is 10 to 16 hours; And / or, the temperature of the first calcination treatment is 400-500° C., and the time of the first calcination treatment is 6-10 hours.

5. The method for preparing the 3D-CuZnAlMg catalyst according to claim 1, characterized in that: In the step (4), the mass ratio of the CuZnAlMg catalyst to polyvinyl alcohol is (40-50): (4-6); And / or, the temperature of the second drying treatment is 40-60° C., and the time of the second drying treatment is 8-14 hours; And / or, the temperature of the second calcination treatment is 750-900° C., and the time of the second calcination treatment is 1-4 hours.

6. The method for preparing the 3D-CuZnAlMg catalyst according to claim 1, characterized in that: In the step (4), the 3D printing further comprises: first 3D printing the mixture of CuZnAlMg catalyst and polyvinyl alcohol into a column, and cutting the column into particles; the column has a diameter of 0.5 to 2 mm and a length of 8 to 12 cm, and the particles have a diameter of 0.5 to 2 mm and a length of 0.5 to 2 mm; And / or, the 3D printing speed is 15-25 mm / s.

7. A 3D-CuZnAlMg catalyst, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 6.

8. The 3D-CuZnAlMg catalyst according to claim 7, characterized in that It comprises CuO, ZnO, Al2O3 and MgO, wherein the content of CuO is 60-75wt%, the content of ZnO is 18-28wt%, the content of Al2O3 is 5-10wt% and the content of MgO is 1-3wt%.

9. Use of the 3D-CuZnAlMg catalyst prepared by the preparation method according to any one of claims 1 to 6 or the 3D-CuZnAlMg catalyst according to any one of claims 7 to 8 in the hydrogenation of carbon dioxide to methanol.

10. A NaA molecular sieve membrane reactor, characterized in that: The catalyst layer comprises a 3D-CuZnAlMg catalyst prepared by the preparation method according to any one of claims 1 to 6 or a 3D-CuZnAlMg catalyst according to any one of claims 7 to 8.